Physico-chemical characterization and tissue healing changes by Hancornia speciosa Gomes latex biomembrane - Pegorin, Giovana S. [UNESP] (2021)
Skin wounds have been a public health concern of high frequency, in addition to requiring intensive and expensive care. The natural rubber latex (NRL) from Hancornia speciosa Gomes has been used to treat many problems in traditional medicine and also present healing properties, antifungal and anti-inflammatory activity and antinociceptive effects. The purpose of this study was to characterize the new biomembrane from the NRL of H. speciosa (HS) by Fourier transform infrared (FTIR) and mechanical strength test and to investigate its biological properties by the cytotoxicity assay and in vivo healing activity. The results showed that the HS biomembrane exhibited characteristic bands of the main component cis-1,4-polyisoprene. Besides, its Young modulus was close to human skin with adhesive-compatible mechanical characteristics. The cytotoxicity assays revealed that the HS biomembrane was not toxic to fibroblast cells neither using agar diffusion test nor MTT assay. Furthermore, the HS biomembrane stimulated the inflammatory cells and the angiogenesis, increased significantly the collagenesis and improved the quality of heal until the remodeling phase induced by implants in mice. Thus, this biomembrane has proven to be a safe and biocompatible biomaterial with healing potential, becoming an effective and low-cost alternative for the treatment of skin wounds.